KOMUNIKASI ANTARBUDAYA SUKU MANGGARAI NUSA TENGGARA TIMUR DI YOGYAKARTA - Stefani Dervin Jano; Christina Rochayanti (Jurnal Paradigma, 2017)
Intercultural communication is communiction made by people who have different cultures, which tend to cause problems. This happened between the people of Manggarai tribe with indigenous people of Yogyakarta in Sleman regency. This study intends explore to analyze the intercultural communication process of Manggarai tribe with indigenous people of Yogyakarta in Sleman District and to identify communication problems between Manggarai tribes and indigenous people of Yogyakarta in Sleman District. This research uses the theory of ethnocentrism, this type of research is qualitative by using descriptive approach, which describes a social phenomenon. In the sense that this study aims to describe something that happens in the field. This study uses data collection techniques with in-depth interviews, observation and literature study. The result of this research is the process of interaction of association which covers cooperation, accomodation, assimilation so that acculturation happens. The other thing is the cultural difference between the indigenous people of Yogyakarta and the Manggarai tribe community. Indigenous people of Yogyakarta have High Context and Femininity culture, while Manggarai tribe people have Low Context and Maskulinity culture. Communication made by the indigenous people of Yogyakarta and Manggarai tribe community through interactive communication phase, transactional and up to the stage of dynamic communication. As for the communication problems that occur are language, food, belief, art and non-verbal language, but both are able to understand, understand and study different cultural problems.